Perancangan Kantor Sewa Di Jakarta Dengan Penerapan Arsitektur Futuristik - Muhammad Fauzan; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
H2O Tower is a middle to upper class Rental Office (Grade A) with complete city facilities and a strategic location. By applying the Futuristic Architecture concept (space) to both building facilities and facade displays. The concept is inspired by the future of space, which in Jakarta has no such futuristic model. By using a facade, the tenant will see that the building impresses the future of space (space). Futuristic concepts mean to lead or towards the future. Futuristic in buildings illustrates that planning and development are not based on something related to the past, but try to describe the future. Buildings must be able to follow and accommodate the demands of activities that are certainly always developing. Characteristics of Futuristic Architecture, namely Architecture that has the characteristics of synthetic materials such as glass, metal, and other advanced building materials, usually affixing to industrial products, Used by other industries not only as buildings, but also as a source of imagination, and so on. . Keywords : Futuristic Architecture, Rental Office